(3aUhd aj GdCSQGQ GdSeGhjIs - (3YWGQO Hf eMeO GdHGHdj GdHZOGOj, MGSH efLe,J (B206 (3g` s ((3eMeO Hf Ydi GdHbGQ s)
(3ChdgG (B:s
(3bGd YWGQO GdefLe (B: (3C (B- (3GdJWHY HGdchGcH eYjf def H(B_ (3GdTeS fjQI Gdadc hSQGL GdYGde hOdjdI Gdedhc heOHQI GdRef s
(3BNQgG (B:s
(3GdchcHGf GdeJfGaQGf ai GdJOHjQ ddCTNGU GdEfSGfjI hPdc dGNJdGa GdchGcH ai GdbSeI cedJ aUhd YWGQO GdefLe, hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3cJHJ gPg GdfSNI HQSe eMeO Hf Ydi Hf EOQjS Gdcheis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B236s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs